Central Retinal Artery Occlusion Associated with Atrial Septal Defect: A Case Report - Gupta, Sharad; Aryal, Manoj; Rajbhandari, Yogita; Adhikari, Ajay; Kamble, Vinit Kumar; Aryal, Binod (Journal of Lumbini Medical College, 2019)
DOI: https://doi.org/10.22502/jlmc.v7i1.281 Introduction: Central retinal artery occlusion (CRAO) is characterized by sudden obstruction of the arterial blood flow in the retinal circulation with consequent ischemic damage to the retina resulting in vision loss. An interesting case of unilateral CRAO associated with atrial septal defect (ASD) in a young female is reported here. Case: A young female presented to emergency department with history of sudden and painless loss of vision in her right eye for one day. Her visual acuity at the time of presentation was perception of light in right eye and 6/6 in left eye. On examination, anterior segments of both the eyes were normal. However, relative afferent pupillary defect was positive in her right eye. On fundus examination, right eye showed pale retina and cherry red spot whereas left eye was unremarkable. Findings were suggestive of right eye CRAO. Ocular massage was done and oral carbonic anhydrase inhibitor was given. Patient was referred to a cardiologist for further evaluation and establishment of the etiology. All tests were within reference limit except a large ASD (secundum type with left to right shunt) with a diameter of 28 mm was revealed on transthoracic echocardiogram. Conclusion: The association between ASD and CRAO is rare. Intracardiac shunts through defect may predispose the disease. Detailed cardiac evaluation is mandatory to rule out possible causes to prevent ocular or systemic embolic events and associated morbidity.